Association Between Serum Vitamin A Levels and Recurrent Respiratory Tract Infections in Children - Wang, Xiaoyan; Li, Xingming; Jin, Chunhua; Bai, Xinyuan; Qi, Xinran; Wang, Jianhong; Zhang, Lili; Li, Na; Jin, Na; Song, Wenhong; Gao, Haitao; Gao, Baojun; et al. (Frontiers in Pediatrics, 2021)
To evaluate the association between serum vitamin A levels and the prevalence of recurrent respiratory tract infections (RRTIs) in children and adolescents and to provide evidence that would help decrease the prevalence of respiratory tract infections (RTIs) in children. This cross-sectional study included 8034 children and adolescents in Beijing aged 6 months to 17 years. RRTI and RTI symptoms were diagnosed according to the Clinical Concept and Management of Recurrent Respiratory Tract Infections in Children. Multivariate logistic regression models were used to evaluate the association between serum vitamin A levels and RRTIs after adjusting for potential confounders. Among the included children, 721 (8.97%) were diagnosed with vitamin A deficiency, whereas 3073 (38.25%) were diagnosed with subclinical vitamin A deficiency. Only 28.8% (208/721) of children with vitamin A deficiency and 53.1% (1631/3073) of children with subclinical vitamin A deficiency had no RRTI and RTI symptoms, respectively. Compared with children with normal vitamin A levels, those with vitamin A deficiency and subclinical vitamin A deficiency had a greater risk for RRTIs, with an odds ratio (OR) of 6.924 [95% confidence interval (CI): 5.433–8.824] and 2.140 (95% CI: 1.825–2.510), respectively]. Vitamin A levels were also positively associated with RTI symptoms, with those having vitamin A deficiency and subclinical vitamin A deficiency showing an OR of 1.126 (95% CI: 0.773–1.640) and 1.216 (95% CI: 1.036–1.427), respectively. The present cross-sectional study found that low serum vitamin A levels were significantly associated with RRTI or RTI prevalence in children and adolescents.